1984
DOI: 10.1007/bf01312939
|View full text |Cite
|
Sign up to set email alerts
|

Is abdominal compression a useful stimulation test for analysis of lower esophageal sphincter function?

Abstract: The change in pressure of competent and incompetent lower esophageal sphincter (LES) due to abdominal compression is still a controversial subject. Therefore, we studied the effect of sustained (SAC) and intermittent (IAC) abdominal compression on lower esophageal sphincter pressure (LESP) in normals (N), patients with hiatus hernia (HH), and patients with scleroderma (S). When resting lower esophageal sphincter pressure exceeded 15 mm Hg, response to SAC and IAC was similar in patients with HH and in normals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Several studies have shown that an increase in Pg can result in a reflex increase in LES tone (4,13,18,22).…”
Section: The Effect Of Cpap On the Lesmentioning
confidence: 99%
“…Several studies have shown that an increase in Pg can result in a reflex increase in LES tone (4,13,18,22).…”
Section: The Effect Of Cpap On the Lesmentioning
confidence: 99%
“…This contraction occurs in continuity with the peristaltic wave of the esophageal body and may represent the response of esophageal body-type circular Short-lived increases in LES pressure also occur secondary to increases in intra-abdominal pressure. Considerable controversy exists as to whether this rise in LES pressure is due to reflex contraction or merely due to passive transmission of the increased intraabdominal pressure (47, 154,269,317,349,360,500). The studies that show this to be a true reflex also suggest that it is vagally mediated and dependent on cholinergic neurons (269,315,360).…”
Section: Reflex Contractions Of the Lo We R Esophageal Sphinctermentioning
confidence: 99%